Survival of Patients With UrAC and Primary BAC and Urothelial Carcinoma With Glandular Differentiation - Wang, Tao; Lv, Zheng; Feng, Huayi; Li, Jinlong; Cui, Bo; Yang, Yang; Huang, Xing; Zhang, Xiangyi; Li, Xintao; Ma, Xin (Frontiers in Oncology, 2022)
Purpose:To investigate the significance of demographic and pathological characteristics on the survival outcomes of urachal adenocarcinoma (UrAC), primary bladder adenocarcinoma (BAC) and urothelial carcinoma with glandular differentiation (UCGD) in China. Materials and Methods:We retrospectively analyzed cases with non-distant metastases (≤ T4M0). Of 106 patients, 30 (28.3%), 40 (37.7%), and 36 (34.0%) met the criteria for UrAC, primary BAC, and UCGD, respectively. Data on patient demographics, tumor pathology, and survival outcomes were collected. The median follow-up was 36 months. Survival was analyzed using multivariate Cox regression. Results:Patients with UrAC were younger (51.87 ± 15.25 years) than those with primary BAC (60.50 ± 12.56 years) and UCGD (63.83 ± 11.60 years) (P<0.001). Patients with UrAC were the most likely to be stage T3–4 (70.0% vs. 40.0% vs. 44.4%; P<0.001), while the primary BAC group had a higher rate of poor differentiation than the UrAC and UCGD groups (57.4% vs. 18.5% vs. 24.1%; P<0.001). The Kaplan–Meier curves showed that the overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS) of the primary BAC group were poorer than those of both the UrAC and UCGD groups (P=0.0046,P<0.0001,P=0.0077 respectively). Regarding BAC, patients with mucinous adenocarcinoma tended to have better OS and PFS than those with other histological types (P<0.005,P=0.0245). Multivariate Cox regression analysis revealed that tumor type (P=0.002), T stage (P=0.034), and the age-adjusted Charlson Comorbidity Index (aCCI) scores (P=0.005) predicted the postoperative OS and DSS of the patients. For PFS, the tumor type (P=0.011), grade (P=0.000), and aCCI (P=0.002) scores were predictive. Conclusion:Among UrAC, primary BAC, and UCGD patients, the prognosis was poorest for those with primary BAC. Attempts should be made to diagnose these aggressive tumors early, since patients in whom tumors are detected early appear to survive longer.